2022
DOI: 10.1177/14604086221112823
|View full text |Cite
|
Sign up to set email alerts
|

Clinical frailty score: A useful tool in predicting outcomes in patients with fragility fractures

Abstract: Introduction Frailty is a known risk factor for falls and subsequent fractures and is linked to greater hospitalisation, morbidity, and mortality in various areas of medicine. A 2017 Trauma Audit and Research Network (TARN) report identified that further research was needed to determine the effect of frailty on outcomes in trauma patients. The UK Best Practice Tariff currently awards a financial incentive for frailty scoring for all patients sustaining major trauma who are managed at Major Trauma Centres (MTCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Frailty is also a known risk factor for fragility fractures. A recent study of hospitalised patients (n = 866) identified that for every stepwise increase in the CFS score, the likelihood of mortality increased [OR values of 1.55 and 1.88 for 30-day and 1-year mortality respectively] [15]. Collectively, these findings highlight that approaches to prevent and manage frailty should also incorporate strategies targeting osteoporosis, sarcopenia, and fragility fractures.…”
Section: What Is Frailty?mentioning
confidence: 95%
See 1 more Smart Citation
“…Frailty is also a known risk factor for fragility fractures. A recent study of hospitalised patients (n = 866) identified that for every stepwise increase in the CFS score, the likelihood of mortality increased [OR values of 1.55 and 1.88 for 30-day and 1-year mortality respectively] [15]. Collectively, these findings highlight that approaches to prevent and manage frailty should also incorporate strategies targeting osteoporosis, sarcopenia, and fragility fractures.…”
Section: What Is Frailty?mentioning
confidence: 95%
“…Frailty is associated with a decline of musculoskeletal, sensory, and neurological systems, which in turn increases falls risk [12,13], likelihood of hip fracture [12,13], and low trauma fragility fractures [5]. In the clinical setting, frailty can predict response to treatment and the likelihood of adverse clinical outcomes, and thus can be used to quantify any likely harms or benefits from proposed medical or surgical interventions [14,15]. For instance, individuals with fragility fractures can be assessed for frailty in acute care and this information may be used to guide patient care planning.…”
Section: Introductionmentioning
confidence: 99%